2020
DOI: 10.1063/5.0028609
|View full text |Cite
|
Sign up to set email alerts
|

Wind load design considerations for the elevation and azimuth drives of a heliostat

Abstract: This paper investigated the dynamic fluctuations of the high-frequency surface pressure and force measurements on an instrumented scale-model heliostat within a turbulent ABL generated in a wind tunnel. Peak aerodynamic load coefficients on the model heliostat calculated following the equivalent static wind load method were consistent with previous wind tunnel studies in the literature. The dynamic analysis of the hinge, azimuth and overturning moments in the current study showed that there are a range of crit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…By applying two criteria of wind speed and direction to the stowing strategy of parts of the heliostat field with similar azimuth angle rather than the whole field, the overall energy yield can be increased during synoptic high-wind periods with a steady wind direction. The operating wind loads on the heliostats that continued operating during high-wind periods were estimated using the wind load coefficients [8] corresponding to azimuth-elevation angle configuration, and comparing with the maximum stow loads to ensure the structural integrity of the supporting pylon, torque tube, drives and foundation.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…By applying two criteria of wind speed and direction to the stowing strategy of parts of the heliostat field with similar azimuth angle rather than the whole field, the overall energy yield can be increased during synoptic high-wind periods with a steady wind direction. The operating wind loads on the heliostats that continued operating during high-wind periods were estimated using the wind load coefficients [8] corresponding to azimuth-elevation angle configuration, and comparing with the maximum stow loads to ensure the structural integrity of the supporting pylon, torque tube, drives and foundation.…”
Section: Methodsmentioning
confidence: 99%
“…Standard practice in the operation of heliostat fields is to stow the entire field during the approach of a high-wind event, such as gust front when the wind speed exceeds this design wind speed. The peak wind loads on heliostats in some operating positions exceed the maximum stow load, depending on the azimuth-elevation configuration of the heliostat and the turbulence intensity and length scales in the atmospheric boundary layer (ABL) simulated in wind tunnel experiments on scale-model heliostats at the University of Adelaide [3,[7][8][9][10][11][12]. It has be shown that the maximum wind loading on the drives and supporting structure during a synoptic gust front with a steady wind direction only applies to a portion of the heliostats in the field, such as azimuth angles of 0° (wind impacting front of heliostat) and 180° (wind impacting back of heliostat) for the hinge moment and overturning moment, and azimuth angles of ±60° and ±120° for the azimuth moment [8].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Analysis of transient load distributions on a scale-model heliostat in the University of Adelaide wind tunnel using the three-sigma approach adopted in the equivalent static wind load design methods implemented by Peterka and Derickson [1] was found to underpredict the maximum hinge moment about the central elevation axis and overturning moment about the base of the pedestal [2]. Further, positive skewness of the von Mises combined stress distributions on the pedestal and torque tube calculated from the measured loads resulted in the three-sigma peak of the Gaussian distribution being underestimated by 6% and 2%, respectively, in comparison with a cumulative probability of 99.7% of the best-fit Gaussian distribution [3].…”
Section: Introductionmentioning
confidence: 99%